2008
DOI: 10.1071/mf07099
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial abundance and production, and their relation to primary production in tropical coastal waters of Peninsular Malaysia

Abstract: In the present study, the relationship between bacteria and phytoplankton in tropical coastal waters was investigated. The bacterial abundance, bacterial production, chlorophyll a concentration and net primary production were measured at several locations in the coastal waters of Peninsular Malaysia. Chlorophyll a concentration ranged from 0.40 to 32.81 μg L–1, whereas bacterial abundance ranged from 0.1 to 97.5 × 106 cells mL–1. Net primary production ranged from 8.49 to 55.95 μg C L–1 h–1, whereas bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 47 publications
6
34
2
Order By: Relevance
“…This concurs with Lee and Bong (2008) who reported high rates of primary and bacterial productivity at Klang relative to the other stations. High TSS was also observed at stations along the Straits of Malacca, and this is often attributed to land clearing activities for construction projects, mining, agricultural and forest industries, and dredging operations (Lee and Bong 2006).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This concurs with Lee and Bong (2008) who reported high rates of primary and bacterial productivity at Klang relative to the other stations. High TSS was also observed at stations along the Straits of Malacca, and this is often attributed to land clearing activities for construction projects, mining, agricultural and forest industries, and dredging operations (Lee and Bong 2006).…”
Section: Discussionsupporting
confidence: 79%
“…High TSS was also observed at stations along the Straits of Malacca, and this is often attributed to land clearing activities for construction projects, mining, agricultural and forest industries, and dredging operations (Lee and Bong 2006). The cfu and bacterial counts obtained in this study were within the range previously reported for Malaysian waters: 100-2500 cfu mL -1 (Lee 2003) and 0.1-97.5 × 10 6 cells mL -1 (Lee and Bong 2008). The ratio of culturable bacteria to total bacteria was from 0.04% to 0.12%, which is similar to Las ufc mL -1 medidas fueron de 0.23 a 1.85 × 10 3 y menores en la estación 2 de Kuantan ( fig.…”
Section: Discussionsupporting
confidence: 67%
“…Surface seawater temperature observed was relatively high and stable, and is typical of tropical coastal waters (Lee and Bong 2008). Salinity was more variable at the Klang estuary due to the Klang River influx.…”
mentioning
confidence: 90%
“…In the classical pathway, phytoplankton production is transferred to higher level via grazing, and subsequently affects fishery yield (Mann 1993) whereas in the microbial pathway, phytoplankton production is coupled to bacterial consumption via the 15 dissolved organic matter pool (Azam et al 1983, del Giorgio et al 1997, Cole 1999. Although the microbial pathway is relatively well-studied in the coastal waters of Peninsular Malaysia (Lee and Bong 2008, Lee et al 2009, Bong and Lee 2011, Lee and Bong 2012, the classical pathway remains poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Primary production during the spring bloom accounts for one-third of the annual production in the bay. Bacterial growth and production are stimulated just after the spring bloom or artificially induced bloom (Lee et al 2001b;Kudo et al 2009). The highest bacterial production in April seemed the result of increased DOM supply after the bloom through exudation, viral lysis or zooplankton grazing.…”
Section: Bacterial Growth and Mortalitymentioning
confidence: 99%